Viral respiratory co-infection in children with presumptive pulmonary TB - a longitudinal study in the pre and post COVID era - Makomba, Robin Sande Aheebla (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMed)--Stellenbosch University, 2024.